Longitudinal progression trajectory of GFR among patients with CKD - Li, Liang; Astor, Brad C; Lewis, Julia; Hu, Bo; Appel, Lawrence J; Lipkowitz, Michael S; Toto, Robert D; Wang, Xuelei; Wright, Jr, Jackson T; Greene, Tom H (American journal of kidney diseases, 2012)
The traditional paradigm of glomerular filtration rate (GFR) progression in patients with chronic kidney disease (CKD) is a steady nearly linear decline over time. We describe individual GFR progression trajectories over 12 years of follow-up in participants in the African American Study of Kidney Disease and Hypertension (AASK). Longitudinal observational study. 846 AASK patients with at least 3 years of follow-up and 8 GFR estimates. Longitudinal GFR estimates from creatinine-based equations. Patient demographic and clinical features. Probability of a nonlinear trajectory and probability of a period of nonprogression calculated for each patient from a Bayesian model of individual estimated GFR (eGFR) trajectories. 352 (41.6%) patients showed a > 0.9 probability of having either a nonlinear trajectory or a prolonged nonprogression period; in 559 (66.1%), the probability was > 0.5. Baseline eGFR > 40 mL/min/1.73 m2 and urine protein-creatinine ratio < 0.22 g/g were associated with a higher likelihood of a nonprogression period. 74 patients (8.7%) had both a substantial period of stable or increasing eGFR and a substantial period of rapid eGFR decrease. Clinical trial population; absence of direct GFR measurements. In contrast to the traditional paradigm of steady GFR progression over time, many patients with CKD have a nonlinear GFR trajectory or a prolonged period of nonprogression. These findings highlight the possibility that stable kidney disease progression can accelerate and, conversely, provide hope that CKD need not be relentlessly progressive. These results should encourage researchers to identify time-dependent factors associated with periods of nonprogression and other desirable trajectories.